2006
DOI: 10.1103/physrevb.73.012501
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of boron-doped diamond

Abstract: We report optical reflectivity study on pure and boron-doped diamond films grown by a hotfilament chemical vapor deposition method. The study reveals the formation of an impurity band close to the top of the valence band upon boron-doping. A schematic picture for the evolution of the electronic structure with boron doping was drawn based on the experimental observation. The study also reveals that the boron doping induces local lattice distortion, which brings an infraredforbidden phonon mode at 1330 cm −1 act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 19 publications
2
51
2
3
Order By: Relevance
“…In addition, B-doping is presented not only in crystalline grains but also at grain boundaries [7]. In these cases, B-doping leads to changes in lattice parameters and introduces acceptor impurity energy levels near the top of the valence band, and consequently, influences the band structure and optoelectronic properties of those B-doped films [1][2][3][4][5]. As important and powerful nondestructive characterization techniques, Raman spectroscopy and X-ray diffraction (XRD) have been extensively proposed to analyze crystalline structure, boron concentration, and residual stress in B-doped diamond films [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, B-doping is presented not only in crystalline grains but also at grain boundaries [7]. In these cases, B-doping leads to changes in lattice parameters and introduces acceptor impurity energy levels near the top of the valence band, and consequently, influences the band structure and optoelectronic properties of those B-doped films [1][2][3][4][5]. As important and powerful nondestructive characterization techniques, Raman spectroscopy and X-ray diffraction (XRD) have been extensively proposed to analyze crystalline structure, boron concentration, and residual stress in B-doped diamond films [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…As important and powerful nondestructive characterization techniques, Raman spectroscopy and X-ray diffraction (XRD) have been extensively proposed to analyze crystalline structure, boron concentration, and residual stress in B-doped diamond films [6,8,9]. In previous work, thick (with thicknesses of more than ten or ten's microns) B-doped diamond films (including CVD freestanding polycrystalline films and single crystals) have been widely studied [3,4,[10][11][12][13][14] and applied in a variety of fields, such as electrochemistry electrodes, superconductors, and diamond-based optoelectronic devices. Since the growth process of thick (freestanding) B-doped films generally takes a long time (10 h or hours in tens), the corresponding B-doping and crystalline structure in the films would be strongly dependent on varying reaction ambient and growth features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 With the premise that the doping level in superconducting diamond is close to the Mott limit the randomly distributed boron atoms, i. e. their random Coulomb potential, may lift the degeneracy of the boron acceptor states leading to a narrow half-filled band from which superconductivity develops. However, spectroscopical studies seem to support the former explanation and rule out the latter suggestion, 29,30 although a complete understanding of the 23,28,31 Recently, a theoretical study suggested the possibility to achieve superconducting transition temperatures on the order of 100 K in C:B due to the exceptionally high Debye temperature of diamond and under the precondition that the doped boron atoms are ordered. 25 In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Boron doped diamond (BDD), prepared either by high pressure high temperature technique (HPHT) [1,2], by plasma enhanced chemical vapour deposition (PECVD) [3][4][5] or by hot filament assisted CVD [6,7], is a unique material which provides the playground for various quantum transport phenomena, such as hopping, weak localization, ballistic transport, unconventional superconductivity and Josephson's effects [8][9][10][11][12]. The growth techniques mentioned above provide boron-doped diamond samples not essentially differing from one another.…”
Section: Introductionmentioning
confidence: 99%